Determinants of capital structure in manufacturing sector : evidence from financial distress firms in Malaysia (2010-2018) / Najwa Syazreen Ismail - Ismail, Najwa Syazreen
The capital structure decision is essential and have a significant role play in incorporate financial management because the need of maximizing returns to the shareholders and thus its impact to the ability to deal with its competitive environment. By using panel data technique, this research attempts to determine the determinants of financial structure in manufacturing financial distress firm in Malaysia for the period of 2010-2018. This research employ secondary data which is annual reports that was obtained in Data Stream. The sample size selected in this study consist of six companies from manufacturing financial distress firm in Malaysia. The dependent variable were used in this study is leverage and the proxy used to represent the dependent variables is total debt to total assets, meanwhile firms size, tangibility, liquidity and growth opportunities act as independent variables. Moreover, regression analysis were used in this research in order to analyse the data. By using Stata version 11, the results shows liquidity has negatively significant relationship with leverage and growth opportunities shows a positively significant relationship with leverage. Meanwhile the remaining independent variables has no significant relationship with leverage. With these findings, there are improvements that could be done in order to enhance the selection of capital structure in capital structure decision making.